KESULITAN GURU DALAM PEMBUATAN MEDIA PEMBELAJARAN IPA KELAS IV SDN 001 SIMPANG TANAH LAPANG KABUPATEN KUANTAN SINGINGI - Sri Indah Wahyuni; Dea Mustika (STKIP Subang, 2024)
The aim of this research is to describe teachers' difficulties in creating science learning media for class IV SDN 001 Simpang Tanah Lapang, Kuantan Singingi Regency. This research method is qualitative research using a descriptive approach. The data source used was the fourth grade homeroom teacher and the school head. The data collection techniques used were interviews, observation and documentation. The data analysis techniques used by Miles and Huberman are data collection, data reduction, data presentation and conclusions. The results of this research show that difficulties in creating learning media were found to exist, lack of teacher ability and creativity in creating learning media that can attract students' learning interest in accordance with the theme and abilities or character of students, lack of teacher understanding in making or using IT-based learning media, obstacles availability of adequate facilities and infrastructure. This shows that the creation of science learning media in Class IV has not been implemented optimally.